Postoperative Management of Lower Extremity Free Tissue Transfer: A Systematic Review - Soteropulos, Carol E.; Chen, Jenny T.; Poore, Samuel O.; Garland, Catharine B. (Journal of Reconstructive Microsurgery, 2019)
Background Free tissue transfer for lower extremity reconstruction is a safe and reliable option for a wide range of challenging wounds; however, no consensus exists regarding postoperative management.Methods A systematic review of postoperative management of lower extremity free tissue transfer was conducted using Medline, Cochrane Database, and Web of Science. Multicenter surveys, randomized controlled trials, cohort studies, and case series were reviewed.Results Fifteen articles investigating current protocols, flap physiology, and aggressive dangle protocols were reviewed. The following evidence-based conclusions were made: (1) Free tissue transfer to the lower extremity is unique due to altered hemodynamics and dependency during orthostasis. Free flap circulation is dependent on locally mediated responses and deprived of compensatory muscular and neurovascular mechanisms that prevent venous congestion in the normal extremity. (2) Compressive wrapping reduces venous congestion and edema and may induce ischemic conditioning, which can increase blood flow. (3) Dangle protocols vary widely in timing of initiation, frequency, and monitoring. Small volume studies examining aggressive mobilization protocols initiating early dependency have led to earlier ambulation and discharge, with no change in flap survival as compared with conservative protocols. (4) Weight bearing may begin after the completion of dangle protocol if no orthopedic injury is present. Conclusions Early initiation of a dangle protocol does not appear to negatively impact flap survival based on this systematic review. Compressive wrapping may be a useful adjunct. Many surgeons agree that clinical monitoring is sufficient; there is no consensus on the utility of adjunct monitoring techniques. Weight bearing may begin after completion of dangle protocol with close flap monitoring, if not prevented by orthopedic restrictions. By providing additional outflow vasculature to reduce venous congestion, flow-through anastomoses may eliminate the need for a dangle protocol. Further research, including large randomized controlled trials is still needed to establish high-level evidence-based conclusions.
Keywords: free tissue transfer; lower extremity reconstruction; lower extremity free flap; dangle protocol; progressive dependency; compressive wrapping